2022
DOI: 10.1002/jctb.7093
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polyhydroxyalkanoates from soil bacterium Bacillus sp. PhNs9

Abstract: Background: Synthetic plastic pollution has increased tremendously over the past few decades. Supplanting synthetic plastics with a biodegradable alternative could save the biosphere from the drastic effects of plastic pollution. Polyhydroxyalkanoates (PHA) have been identified with the potential to become a feasible option.Results: A bacterial strain isolated from pavement soil was investigated for its PHA production ability. The isolated strain was found to be non-virulent, and susceptible to various antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Brdlík et al ( 2021) observed a 16% weight loss in PLA under composting conditions over 60 days [27]. This aligns with the findings of Karamanlioglu et al (2017), who reported a 20% weight reduction in PLA over 20 months in soil [28]. Notably, controlled composting with bacterial treatment resulted in the complete degradation of PLA within 60 days as indicated in (Figure 2) [29].…”
Section: Biodegradability Of Bioplastic In Complex Environmental Cond...supporting
confidence: 68%
“…Brdlík et al ( 2021) observed a 16% weight loss in PLA under composting conditions over 60 days [27]. This aligns with the findings of Karamanlioglu et al (2017), who reported a 20% weight reduction in PLA over 20 months in soil [28]. Notably, controlled composting with bacterial treatment resulted in the complete degradation of PLA within 60 days as indicated in (Figure 2) [29].…”
Section: Biodegradability Of Bioplastic In Complex Environmental Cond...supporting
confidence: 68%
“…Aliphatic esters such as polyhydroxyalkanoate (PHA) and polylactic acid (PLA) have been recognized as valuable alternatives to petro-plastics [ 18 , 19 ]. In particular, polyhydroxyalkanoates (PHAs) are emerging as versatile building blocks for plastic production and they are fully biocompatible and biodegradable in many environments [ 20 , 21 ]. PLA is another useful candidate obtained from renewable feedstocks and with low production costs, but for example, it showed some limitations regarding the degradation in seawater [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simple and efficient production techniques of bioplastics will help to move away from the use of synthetic plastics and assist in reducing plastic pollution in the environment. The second article by Patil et al 5 investigates the synthesis and characterization of PHAs from soil bacterium Bacillus sp. PhNs9.…”
mentioning
confidence: 99%